Comparison of short-term clinical efficacy between modified Kamikawa anastomosis and double tract anastomosis after laparoscopic proximal gastrectomy - Wu, Chu-Ying; Huang, Qiao-Zhen (Frontiers in Oncology, 2024)
ObjectiveThis study aimed to explore the short-term clinical efficacy of modified Kamikawa anastomosis and double tract anastomosis after laparoscopic proximal gastrectomy.MethodsA retrospective analysis was carried out by collecting the clinical and pathological data of 42 patients who underwent laparoscopic proximal gastrectomy after admission in our centre from May 2020 to October 2022. Among the 42 enrolled patients, 22 underwent modified Kamikawa anastomosis (modified Kamikawa group), and the other 20 underwent double tract anastomosis (double tract group). Outcome measures included intraoperative condition, postoperative recovery, postoperative quality of life, postoperative nutritional status and gastroesophageal reflux. The patients were followed up using outpatient examination and telephone interviews to identify their nutritional status, reflux esophagitis and anastomotic status.Results(1) Intraoperative condition: Compared with the double tract group, the modified Kamikawa group had significantly prolonged time for operation and digestive tract reconstruction. However, no statistically significant difference in intraoperative blood loss was found between the two groups. (2) Postoperative recovery: Compared with the double tract group, the modified Kamikawa group had a significantly shorter time for the first postoperative intake of fluids, drainage tube placement and postoperative hospital stay. No statistically significant difference in the time to first postoperative anal exhaust and postoperative complications was found between the two groups. (3) Postoperative quality of life: Compared with the double tract group, the modified Kamikawa group showed better quality of life at 12 months after surgery. (4) Postoperative nutritional status and gastroesophageal reflux: No statistically significant difference in hemoglobin, total serum albumin, albumin, body mass index, MUST score, PG-SGA score, grading of reflux esophagitis using the Los Angeles classification system and GERD score was found between the two groups at 6 and 12 months after surgery. All patients did not experience anastomotic stenosis and tumour recurrence or metastasis.ConclusionsModified Kamikawa anastomosis is a safe and feasible treatment in laparoscopic proximal gastrectomy, which can ensure good postoperative anti-reflux effect and nutritional status. It has the advantage of better postoperative recorvery and quality of life compared with double tract anastomosis.